Empowering sex workers in India to reduce vulnerability to HIV and sexually transmitted diseases - Swendeman, Dallas (2009)
The Sonagachi Project was initiated in Kolkata, India in 1992 as a STD/HIV intervention for sex workers. The project evolved to adopt strategies common to women’s empowerment programs globally (i.e., community mobilization, rights-based framing, advocacy, micro-finance) to address common factors that support effective, evidence-based HIV/STD prevention. The Sonagachi model is now a broadly diffused evidence-based empowerment program. We previously demonstrated significant condom use increases among female sex workers in a 16 month replication trial of the Sonagachi empowerment intervention (n = 110) compared to a control community (n = 106) receiving standard care of STD clinic, condom promotion, and peer education in two randomly assigned rural towns in West Bengal, India (Basu et al., 2004). This article examines the intervention’s impacts on 21 measured variables reflecting five common factors of effective HIV/STD prevention programs to estimate the impact of empowerment strategies on HIV/STD prevention program goals. The intervention which was conducted in 2000–2001 significantly: 1) improved knowledge of STDs and condom protection from STD and HIV, and maintained STD/HIV risk perceptions despite treatment; 2) provided a frame to motivate change based on reframing sex work as valid work, increasing disclosure of profession, and instilling a hopeful future orientation reflected in desire for more education or training; 3) improved skills in sexual and workplace negotiations reflected in increased refusal, condom decision-making, and ability to change work contract, but not ability to take leave; 4) built social support by increasing social interactions outside work, social function participation, and helping other sex workers; and 5) addressed environmental barriers of economic vulnerabilities by increasing savings and alternative income, but not working in other locations, nor reduced loan taking, and did not increase voting to build social capital. This study’s results demonstrate that, compared to narrowcast clinical and prevention services alone, empowerment strategies can significantly impact a broader range of factors to reduce vulnerability to HIV/STDs.